2020
DOI: 10.1111/1440-1681.13298
|View full text |Cite
|
Sign up to set email alerts
|

GYY4137 exhibits anti‐atherosclerosis effect in apolipoprotein E (−/−) mice via PI3K/Akt and TLR4 signalling

Abstract: Hydrogen sulphide (H 2 S) had been suggested to be involved in the pathogenesis of atherosclerosis, but the underlying molecular mechanisms are poorly understood.In this study, we aimed to investigate the anti-atherosclerosis effect of morpholin-4-ium-methoxyphenyl-morpholino-phosphinodithioate (GYY4137) in RAW264.7 cell-derived foam cells formation and in the atherosclerotic plaque of ApoE−/− mice fed with a high-fat diet, and study the underlying mechanisms of phosphatidylinositol 3-kinase (PI3K), serine/ th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…PI3K/Akt signaling was recently suggested to negatively regulate TLR4-mediated inflammation. Zheng Y et al first confirmed that morpholin-4-ium-methoxyphenyl-morpholinophosphinodithioate (GYY4137) improves foam cell formation in vitro through the PI3K/AKT and TLR4 pathways and reduces the expression of proinflammatory cytokines, thus reducing the source of foam cells and lipid volume in unstable plaque tissues (Zheng et al, 2020). The NF-κB signaling pathway has been shown in several studies to be involved in the inflammation of atherosclerotic plaques.…”
Section: Effects Of Pi3k On Atherosclerotic Plaque Formationmentioning
confidence: 98%
“…PI3K/Akt signaling was recently suggested to negatively regulate TLR4-mediated inflammation. Zheng Y et al first confirmed that morpholin-4-ium-methoxyphenyl-morpholinophosphinodithioate (GYY4137) improves foam cell formation in vitro through the PI3K/AKT and TLR4 pathways and reduces the expression of proinflammatory cytokines, thus reducing the source of foam cells and lipid volume in unstable plaque tissues (Zheng et al, 2020). The NF-κB signaling pathway has been shown in several studies to be involved in the inflammation of atherosclerotic plaques.…”
Section: Effects Of Pi3k On Atherosclerotic Plaque Formationmentioning
confidence: 98%
“…In a rat stomach culture model, GYY4137 increased phosphorylation of Akt and suppressed the secretion of the hunger hormone Ghrelin [ 49 ]. In apolipoprotein E KO mice, GYY4137 activated the PI3K/Akt pathway and reduced TLR4 expression, which was critical in preventing atherosclerotic plaque formation [ 50 ].…”
Section: H 2 S Regulates Different Cellular Proces...mentioning
confidence: 99%
“… The PI3K/Akt signaling pathway. H 2 S donors (GYY4137 and NaHS) increase Akt activation, as shown in red font, arrow and lines [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Created with BioRender.com.…”
Section: Figurementioning
confidence: 99%
“…In a study by Qiu et al, diabetic model rats who were administered GYY4137 before myocardial ischemiareperfusion injury showed smaller infarcts, reduced apoptosis, and lower oxidative stress than the control group, implying that the protective effect of GYY4137 against myocardial ischemiareperfusion injury is linked to p-Akt and nuclear Nrf2 protein (73). In addition, Zheng et al employed GYY4137 to show that H 2 S molecules regulate the PI3K/Akt/TLR4 signaling pathway to stabilize vascular plaques (74). As research continues, the atherosclerotic potential of GYY4137 is increasingly being unraveled, such as prevention of vascular inflammation and oxidative stress (75), protection against myocardial fibrosis (18), and attenuation of adverse remodeling (76).…”
Section: Gyymentioning
confidence: 99%